Wide-Area backup protection against asymmetrical faults in the presence of renewable energy sources - Rezaei Jegarluei, Mohammad; Aristidou, Petros; Azizi, Sadegh (My University, 2023)
Conventional protection schemes have essentially been developed for power systems dominated by synchronous generators. High penetration of power-electronic interfaced renewable energy sources (PEIRESs) can adversely impact the reliability of protection systems, thereby increasing the risk of widespread disturbances. This paper proposes a robust wide-area backup protection (WABP) scheme against asymmetrical faults for transmission systems with high penetration of renewables. The scheme exploits the full potential of available synchrophasors without placing any rigid constraints on PMU locations. To this end, the faulted line and a few appropriately selected PEIRESs are replaced by equivalent current sources using the Substitution Theorem. The remaining PEIRESs are substituted by their equivalent impedances accounting for their response to a fault, considering the control strategies and overcurrent limits of these PEIRESs. This results in a linear system of equations whose solution readily indicates the faulted line on account of the weighted sum of squared residuals (WSSR) concept. To add to the security of the proposed scheme, the fault distance on the pinpointed line is also calculated and checked to ensure it lies within the acceptable range. A total of more than 80,000 simulations conducted on the IEEE 39-bus test system verify that the proposed scheme performs properly irrespective of the numbers/locations of PEIRESs and their control strategies.
Keywords: Wide area backup protection; Phasor measurement unit (PMU); Renewable energy sources; Superimposed circuits